(untitled) (Ozone Therapy Global Journal, 2019)
Recurrent Chronic mastitis is a rare condition in benign breast pathology, the poor results obtained with the most commonly used therapeutic procedures, motivates the review and presentation of a case. I present the case of a female patient of 38 years old, married, last date childbirth 4 years ago, no birth control, Fibrocystic Mastopathy and fibroadenoma surgery 20 years ago was studied. It develops a painful right breast mass with signs of progressive onset phlogosis at the end of October 2018. With the Objective of Confirming the benefits of ozone therapy as a coadjutant in benign breast inflammatory pathology, is applied to this patient already treated with antibiotics and corticosteroids by diagnosis of chronic mastitis confirmed by pathological anatomy, without clinical improvement a month after the begining of conventional management, - Laboratory tests without altered findings, - Monthly serial ultrasound, - Chronic use of antibiotics, three serial drainages, The Ozone Generator MD 600 I, Natur - Ozone, was used to Local ozone therapy with glass bell 3-2 times per week at 40-30 µg/mL for 10 sessions, - Systemic ozone therapy with ozonated saline solution (SSO3) 3-2 times per week, at 6 µg /mL, for 10 sessions, then 5 sessions at 5 µg/mL twice a week, - Local ozone therapy with infiltration in lesions and mesotherapy of 10-20 mL at 30 µg/mL for 6 sessions, finally, ozonated saline solution was continued until healing of external lesions at a concentration of 3 µg/mL. The Results were the rapid resolution of the symptomatology and clinical improvement after the sixth session: less pain, less erythema, decrease in volume of the mass and collections, the corticoid was removed after a resonance confirming improvement of the findings of images. Discussion: being an uncommon condition, difficult to diagnose and treat, and especially a chronic evolution that can take 6 months to years of recurrence, we try to introduce adjuvant therapy such as ozone therapy to improve prognosis and shorten the evolution of pathology. Conclusions: The association of local and systemic ozone therapy with medical surgical support is evaluated as an alternative to obtain better and faster results that has to be validated: 1. Reduces recovery time and improves signs and symptoms. 2. Reduces the costs of medications and their side effects. 3. Prevents recurrences of inflammatory processes. 4. Improve the Redox environment of the patient being treated..